Scalable Enantioselective Synthesis of Fmoc‐β2‐Serine and Fmoc‐β2‐Threonine by an Organocatalytic Mannich Reaction. Issue 22 (18th June 2015) - Meyer, Daniel; Marti, Roger; Seebach, Dieter
Abstract: The diastereoselective Mannich reaction of functionalized aldehydes, using a phenethylamine‐derived iminium precursor, by activation with prolines and prolinol derivatives have been studied. Optimized reaction conditions have been developed, allowing for scale‐up and preparation of γ‐amino alcohol derivatives on multi‐gram scale from β‐hydroxypropanal and ‐butanal, with diastereoselectivites of typically >73:27 and yields of >60 %. After chromatographic diastereoisomer separation, hydrogenolytic debenzylation, enantiomerically pure Fmoc‐β 2 ‐Ser( t Bu)‐OH and Fmoc‐β 2 ‐Thr( t Bu)‐OH were thus prepared on multi‐gram scale in 6 steps and with overall yields of 24 % and 10 %, respectively, starting from commercially available starting compounds. Abstract : The scalable diastereoselective Mannich reaction of functionalized aldehydes with phenethylamine‐derived iminium precursors, by activation with prolines and prolinol derivatives is reported. The new robust process allows the simple preparation of enantiomerically pure Fmoc‐protected β 2 ‐serine and β 2 ‐threonine on multi‐gram quantities.